Experimental Investigation on Ignition Effects of Fuel Tank Impacted by Bi2O3-Reinforced PTFE/Al Reactive Material Projectile - Ruiqi Wang; Qin Yin; Miao Yao; Junyi Huang; Rongxin Li; Zhenru Gao; Shuangzhang Wu; Yuchun Li; Jiaxiang Wu (Metals, 2023)
A series of impact fuel tank experiments are carried out through the ballistic impact method. The ignition abilities of Bi2O3-reinforced PTFE/Al reactive material, metal aluminum, and inert metal steel are compared and analyzed, and the ignition mode of kerosene is explored when PTFE/Al/Bi2O3 impacts the fuel tank at different velocities. The results offer that PTFE/Al/Bi2O3 reactive material has outstanding ignition ability, and the order for ignition ability is PTFE/Al/Bi2O3 reactive material, metal aluminum, and inert metal steel. The kerosene content of the fuel tank has a significant impact on the ignition effect. The ignition effect of PTFE/Al/Bi2O3 reactive material impacting the fuel tank filled with 50% kerosene is weaker than that impacting the full tank. Under different impact velocities, PTFE/Al/Bi2O3 reactive materials display diverse ignition modes for kerosene: kerosene is directly ignited by the flame in the reverse reaction zone under low-velocity conditions, while high-temperature-activated reactive fragments are the ignition heat source of high-velocity conditions.